Ablation of a life-threatening arrhythmia in a patient with Brugada syndrome - Kamel, Omnia (Glob Cardiol Sci Pract, 2021)
Brugada syndrome is an autosomal dominant arrhythmogenic disease associated with an increased risk of ventricular fibrillation and sudden cardiac death. The mainstay of treatment in high-risk patients is an implantable cardioverter-defibrillator (ICD), however radiofrequency ablation has been proposed over the past decade as an additional therapy in patients with recurrent ICD firing. We report a case of Brugada syndrome with an electrical storm which was successfully managed by radiofrequency ablation.